Understanding and Enhancing the Effectiveness of Adaptive Reuse of Built Heritage - Fatemeh Hedieh Arfa (A+BE: Architecture and the Built Environment)
Adaptive Reuse (AR) of heritage buildings is a sustainable approach to preserving cultural heritage while accommodating new functions. Despite the growing importance of AR in the last decades, a lack of comprehensive models for AR, particularly concerning heritage buildings, persists. This research addresses this gap by developing a model that guides architects in the AR process, drawing on international literature and Dutch AR practices, with a focus on its adaptation and possible application in the Iranian context.